2021
DOI: 10.1007/s11154-021-09691-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the levothyroxine dose in the hormone replacement therapy of primary hypothyroidism in adults

Abstract: Levothyroxine (LT4) is a safe, effective means of hormone replacement therapy for hypothyroidism. Here, we review the pharmaceutical, pathophysiological and behavioural factors influencing the absorption, distribution, metabolism and excretion of LT4. Any factor that alters the state of the epithelium in the stomach or small intestine will reduce and/or slow absorption of LT4; these include ulcerative colitis, coeliac disease, bariatric surgery, Helicobacter pylori infection, food intolerance, gastritis, miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 158 publications
(179 reference statements)
0
12
0
1
Order By: Relevance
“…In this study, The TSH of thyroid function in the intervention group was lower than that before treatment, and the level of thyroid function was stable below the target value of treatment.Talebi S et al 9 found that supplementation of probiotics and prebiotics on the basis of levothyroxine could signi cantly reduce the level of TSH, which was consistent with our results.This shows that, for patients with well-controlled thyroid function in the second trimester, the combined application of probiotics and prebiotics is bene cial to maintain the stability of thyroid function. Levothyroxine sodium is absorbed mainly in the small intestine 33 , and as mentioned above, SIBO status disrupts the intestinal barrier, and we hypothesized that probiotics and prebiotics may improve the intestinal barrier and promote the absorption of LT4. Second, gut bacteria can express β-glucuronidase and sulfatase to inactivate thyroid hormones in the liver 9 ,and study has shown that Lactobacillus acidophilus can signi cantly reduce the βglucuronidase activity in feces.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, The TSH of thyroid function in the intervention group was lower than that before treatment, and the level of thyroid function was stable below the target value of treatment.Talebi S et al 9 found that supplementation of probiotics and prebiotics on the basis of levothyroxine could signi cantly reduce the level of TSH, which was consistent with our results.This shows that, for patients with well-controlled thyroid function in the second trimester, the combined application of probiotics and prebiotics is bene cial to maintain the stability of thyroid function. Levothyroxine sodium is absorbed mainly in the small intestine 33 , and as mentioned above, SIBO status disrupts the intestinal barrier, and we hypothesized that probiotics and prebiotics may improve the intestinal barrier and promote the absorption of LT4. Second, gut bacteria can express β-glucuronidase and sulfatase to inactivate thyroid hormones in the liver 9 ,and study has shown that Lactobacillus acidophilus can signi cantly reduce the βglucuronidase activity in feces.…”
Section: Discussionmentioning
confidence: 91%
“…In patients requiring unusually high LT4 doses, investigate other factors apart from compliance and concomitant medications, including gastrointestinal tract malabsorption, concomitant food and drink, and Helicobacter pylori infection. 26 - 28 …”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used route of LT4 administration is per os, resulting in intestinal absorption of 60 to 80% of the ingested dose [ 27 ]. Since the absorption is variable and LT4 has a narrow therapeutic index, caution is required in dose individualization and in the mode of ingestion, as well as in ensuring patient compliance [ 24 , 28 ]. However, a long road lies ahead until an optimal LT4 therapeutic target is achieved, which fact has recently been summarized [ 28 ].…”
Section: The Problems Involved In Optimization Of Lt4 Dosementioning
confidence: 99%
“…Since the absorption is variable and LT4 has a narrow therapeutic index, caution is required in dose individualization and in the mode of ingestion, as well as in ensuring patient compliance [ 24 , 28 ]. However, a long road lies ahead until an optimal LT4 therapeutic target is achieved, which fact has recently been summarized [ 28 ]. One of the issues specific to thyroidectomized patients is the timing of pharmacologic thyroid homeostasis recovery [ 24 ].…”
Section: The Problems Involved In Optimization Of Lt4 Dosementioning
confidence: 99%